NEEDS ANALYSIS FOR THE DEVELOPMENT OF A CHARACTER EDUCATION LEARNING MODEL BASED ON LOCAL CULTURE - Susanti, Atika (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
The rapid development of globalization demands that education focus not only on academic aspects but also on the preservation of cultural identity and the development of students' character. The primary objective of this study is to analyze the needs for developing a character education learning model based on local culture. The method used in this study is descriptive quantitative, involving 100 elementary school teachers from 10 cities and regencies in Bengkulu Province as participants. Data were collected through needs assessment questionnaires, curriculum analysis, and student characteristic analysis, and were then analyzed using descriptive quantitative analysis techniques. The results showed that 92% of teachers agreed that culturally based learning helps students understand character values, 88% stated it enhances student engagement, and 90% expressed the need for a learning model grounded in local culture. Furthermore, 94% of teachers preferred a model that involves direct experiences such as discussions and cultural exploration. However, 87% acknowledged the absence of a systematic model to integrate local culture and character values. Curriculum analysis indicated that the proposed learning model is relevant to be applied in the elements of Bhinneka Tunggal Ika and NKRI from grades 1 to 6. Cognitively, elementary students are at the concrete operational stage, showing a tendency to learn through direct experiences and tangible objects. Psychologically and socially, they enjoy playing, interacting with peers, and are beginning to develop social skills such as cooperation, empathy, and conflict resolution. Therefore, the development of a character education model based on local culture is urgently needed and considered feasible for systematic implementation in the learning process.